Effect of ambient temperature on cardiovascular drift and maximal oxygen uptake - Lafrenz, A. J.; Wingo, J. E.; Ganio, M. S.; Cureton, K. J. (Medicine & Science in Sports & Exercise, 2008)
Purpose: This study tested the hypothesis that the magnitude of cardiovascular (CV) drift and decrease in maximal oxygen uptake (VO2max) would be greater at 35°C than at 22°C.